Menganalisis Hubungan antara Fisik Literasi dan Minat Siswa Serta Aktivitas Fisik Siswa Kelas 7 SMPN 11 Muaro Jambi Terhadap Olahraga Bulu Tangkis - Tri Hadi Prayogi; Ugi Nugraha; Mohd. Adrizal (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to examine the relationship between physical literacy, students’ interest, and physical activity in badminton among junior high school students. This research employed a quantitative correlational design. The participants were 30 seventh-grade students from SMPN 11 Muaro Jambi selected using purposive sampling. Data were collected through questionnaires measuring students’ interest, physical activity, and physical literacy based on a Likert scale. Data analysis techniques included descriptive statistics, Pearson product-moment correlation, and multiple linear regression. The results showed a significant positive relationship between students’ interest and physical literacy (r = 0.62, p < 0.05), as well as between physical activity and physical literacy (r = 0.58, p < 0.05). Furthermore, students’ interest and physical activity simultaneously contributed 52% to physical literacy. In conclusion, increasing students’ interest and levels of physical activity plays an important role in developing physical literacy through badminton activities at school. Keywords: Physical Activity, Badminton, Physical Literacy, Students’ Interest